2020
DOI: 10.1111/jvim.15876
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil extracellular traps in stored canine red blood cell units

Abstract: Background: Neutrophil extracellular traps (NETs), webs of DNA and citrullinated histones extruded from activated neutrophils cause transfusion-related acute lung injury. Supernatants of stored red blood cell (RBC) units might promote NETosis in neutrophils from the units or from transfusion recipients. Hypotheses: (1) NETs form during storage of canine RBC, (2) leukoreduction (LR) before storage of RBC reduces NETosis, and (3) supernatant from stored, nonleukoreduced (NLR) RBC units induces NETosis in healthy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 46 publications
1
5
0
Order By: Relevance
“…In our study, leukoreduction successfully met the US FDA threshold of 5 × 10 6 WBC/unit 21 and the less than 1 × 10 6 WBC/unit standard of the Council of Europe 22 . Moreover, leukoreduction caused an almost complete platelets' depletion, confirming the reduction greater than 99% in LR blood canine units 23 . In cold‐stored WB, the platelet count declines by 1% to 2% per day, with limited impact on clotting time or on clot strength as measured by thromboelastography.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…In our study, leukoreduction successfully met the US FDA threshold of 5 × 10 6 WBC/unit 21 and the less than 1 × 10 6 WBC/unit standard of the Council of Europe 22 . Moreover, leukoreduction caused an almost complete platelets' depletion, confirming the reduction greater than 99% in LR blood canine units 23 . In cold‐stored WB, the platelet count declines by 1% to 2% per day, with limited impact on clotting time or on clot strength as measured by thromboelastography.…”
Section: Discussionsupporting
confidence: 58%
“…22 Moreover, leukoreduction caused an almost complete platelets' depletion, confirming the reduction greater than 99% in LR blood canine units. 23 In cold-stored WB, the platelet count declines by 1% to 2% per day, with limited impact on clotting time or on clot strength as measured by T A B L E 2 Mean levels and SDs of coagulation variables in whole blood at different sampling times (T0, T35) and in fresh frozen plasma at 1 year of storage thromboelastography. Animal studies have confirmed that platelets from stored WB participate in clot formation.…”
Section: Discussionmentioning
confidence: 99%
“…Comparison with platelet-deprived blood products would help to explain the source of MDA in CPDA-1-stored whole blood supernatant. The increase in MDA may also be linked to neutrophil activation and ROS generation, with subsequent oxidation of polyunsaturated lipids, as leukocyte activation in stored canine blood products has been described [17,21]. Studies on human blood products also suggest that early MDA formation may be linked to leukocytes or platelets because the MDA concentration in stored human erythrocytes was shown to increase over time, whereas that measured in the supernatant of RBC concentrates was unchanged [39,40].…”
Section: Discussionmentioning
confidence: 99%
“…Some ex vivo aging processes have been studied in dog blood, with results indicating release of proinflammatory cytokines and microparticles, changes in erythrocyte volume, potassium release and ATP and 2,3-DPG depletion, along with other biochemical alterations [9,[15][16][17][18]. It was also shown that the presence of leukocytes may partially perpetuate several metabolic disarrangements in canine preserved blood [19][20][21]. Nevertheless, it remains unclear how fast redox system imbalances occur and to what extent oxidative stress correlates with other 'storage lesions' .…”
Section: Introductionmentioning
confidence: 99%
“…The results indicated that NET markers were increased in stored red blood cells, and demonstrated that leukoreduced red blood cells prior to storage, reduced NET formation. 229 Neutrophils play an important role in TRALI pathogenesis. 230 In a neutrophil and platelet-dependent mouse model of TRALI, NETs were present in the lung microvasculature and plasma.…”
Section: Experimental Lung Injury - Acute Lung Inflammatory Modelsmentioning
confidence: 99%